2019
DOI: 10.1021/acsnano.8b09689
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Topology of Nanoscale Skyrmion Bubbles by Spatially Geometric Confinement

Abstract: The discovery of magnetic skyrmion bubbles in centrosymmetric magnets has been receiving increasing interest from the research community, due to the fascinating physics of topological spin textures and its possible applications to spintronics. However, key challenges remain, such as how to manipulate the nucleation of skyrmion bubbles to exclude the trivial bubbles or metastable skyrmion bubbles that usually coexist with skyrmion bubbles in the centrosymmetric magnets. Here, we report having successfully perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 50 publications
6
49
0
Order By: Relevance
“…However, few skyrmions are retained at zero magnetic field. This feature further suggests that the magnetic hysteretic effect in our experiments mainly originates from the geometrical pinning effect of the nano-dots, as reported in the previous literatures 9 , 39 , 40 . For the non-volatility of vortex, the case is different.…”
Section: Resultssupporting
confidence: 90%
“…However, few skyrmions are retained at zero magnetic field. This feature further suggests that the magnetic hysteretic effect in our experiments mainly originates from the geometrical pinning effect of the nano-dots, as reported in the previous literatures 9 , 39 , 40 . For the non-volatility of vortex, the case is different.…”
Section: Resultssupporting
confidence: 90%
“…[ 98,99 ] In 2017, Hou et al first experimentally observed skyrmionic magnetic bubbles at room temperature in a frustrated Fe 3 Sn 2 magnet with Kagome lattice by using LTEM (Figure 2f–h). [ 129,130 ] In 2019, Kurumaji et al. demonstrated a Bloch‐type skyrmion state in a frustrated centrosymmetric triangular‐lattice magnet Gd 2 PdSi 3 .…”
Section: Topological Structures In Magnetic Thin Films and Heterostrumentioning
confidence: 99%
“…There are five types of alloys in the Fe-Sn compounds family, that is Fe3Sn, Fe5Sn3 and Fe3Sn2, FeSn, and FeSn2, and all of these alloys show a magnetic ordering temperature well above the RT. Among these alloys, the frustrated kagome magnet Fe3Sn2 have emerged as an important class of the magnetic topological materials in recent years because it exhibits many interesting physical properties, such as skyrmions [31][32][33][34] , massive Dirac fermions 35 , many-body spin-orbit tunability 36 , flatbands 37 , de-Haas-Van Alphen effect 38 , and the large THE above the RT 16 . Furthermore, the kagome antiferromagnetic FeSn also exhibits profound relation with some interesting physical properties such as Dirac fermions and flatbands 39 .…”
mentioning
confidence: 99%